Presurgical nasoalveolar molding in patients with unilateral and bilateral clefts-changing concepts and current approach - Taruna Puri; Dolly Patel (Wolters Kluwer Medknow Publications, 2015)
Nasoalveolar reconstruction for patients with cleft lip and palate is a challenging job for the surgeon. Many procedures to obtain esthetic results and decrease the cleft gap have been suggested. Presurgical nasoalveolar molding is used as an adjunct for reshaping the alveolar and nasal segments prior to surgical repair. Rehabilitation of cleft lip and palate usually requires a team approach which includes a plastic surgeon, orthodontist, speech therapist, pediatrician and a prosthodontist. In the recent times there have been many controversies regarding the same concept. This paper describes the changing concepts in the treatment of patients with cleft lip and palate, discusses the various views given by different individuals, focuses on the current concepts and also on the long-term benefits of the same. With time, the concept of treatment of cleft lip and palate has changed. Nowadays more emphasis is laid on the nasal and alveolar molding prior to the primary surgical lip repair. This molding reduces the number of revision surgeries to be performed later.